The Relationship between Family Function and Anxiety Level of Chronic Kidney Failure Patients Undergoing Hemodialysis Therapy in the Hemodialysis Room - Ayu A, Komang Ellia; Windarwati, Heni Dwi; Ulya, Ikhda (Promotion and Prevention in Mental Health Journal, 2023)
The psychological impact of patients undergoing Hemodialysis is anxiety. Patients are anxious about the sustainability of their lives that depend on Hemodialysis. Anxiety is influenced by various factors, one of which is the incompatibility of family functions due to GGK disease, which requires hemodialysis therapy. This study aims to analyze the relationship between family function and anxiety of GGK patients undergoing Hemodialysis in the Hemodialysis Room of a Hospital in Malang. Observational design: The respondents were all HD patients in the Hemodialysis Room of the Hospital in Malang, totaling 80 respondents determined by purposive sampling. Data were collected by questionnaire. Data analysis using Spearman Rho test. The results showed a significant relationship between family function (p=0.002 or p<0.05)x and anxiety level. Conclusion: There is a significant relationship between family function and the anxiety level of hemodialysis patients. It is recommended that nurses facilitate forming family groups of patients with GGK to build communication networks, mutual support, and information bridges with health workers.